Simplifying Oral health evaluation: a novel approach through single-item surveys - Takashi Zaitsu; Tomoya Saito; Akiko Oshiro; Yoko Kawaguchi; Ichiro Kawachi (BMC, 2024)
Abstract Background This study adopts a novel approach of using single-item surveys to simplify the assessment of oral health status and behaviors among Japanese private sector employees. We aimed to establish the validity of self-reported oral health in relation to clinical dental examinations, and to elucidate the relationship between oral diseases, health behaviors, and self-assessments. A secondary aim was to explore the association of self-rated oral health with oral health behaviors. Materials and methods Self-administered questionnaires and dental examinations were obtained from 2262 Japanese private sector employees. Workers self-rated their overall oral health status according to five choices: "very good," "good," "fair," "poor," or "bad." Self-reports were then compared with the results of clinical dental examinations, which included measuring the oral hygiene index (DI-S), the number of decayed teeth, periodontal status (Community Periodontal Index) and number of missing teeth. Convergent validity was also tested by examining the correlations of self-reported oral health status with oral health behaviors. Results Overall, 30.8% of workers reported their oral health as "poor" or "bad." "Poor" or "bad" oral health status was significantly correlated with missing teeth, periodontitis, and decayed teeth. However, lower correlations were found for gingivitis and the oral hygiene index. Most self-reported oral health behaviors were correlated with self-rated oral health; exceptions were "tooth brushing instructions received in a dental clinic," "having a primary-care dentist," and "habitual snacking between meals." Conclusions Self-rated oral health provides reasonably valid data, and correlated well with clinically assessed oral health status, including dental caries, periodontal status, and tooth loss. Convergent validity was also found for oral health behaviors. Trial registration Clinical trial registration number: UMIN000023011 (UMIN-CTR). Date of clinical trial registration: 06/07/2016.